The Use of Radar Sensors toTrack Marine Pollution, the Studied Area: Iran's Marine Area - Majid Hosseini Hamid; Mehrnaz Farzin Gohar; Masoud Sadri Nasab; Behzad Layeghi (Nīvār)
Based on theory, this research investigated the relationship between the penetration depth of electromagnetic waves and the conductivity of sea water based on daily parameters of temperature and salinity in Caspian Sea with low salinity and Oman Sea with high salinity. The data was received from the oceanographic center over a period of one year and the values are calculated daily and the results show that the wave range is more sensitive to salinity. The range decreases with the increase of the frequency, so that at the frequency of 1000 khz, the range for the Caspian Sea and Oman reached about 2 and 5 cm, respectively. The range in the low frequency of 100 Hz has increased significantly and its value for the Caspian Sea is 1.51 m in March (T=11.76 C0, P=7.59psu) and for the Oman Sea it is 16.22 m in January (T=22 C0 , P=36.5 psu) was obtained. Also, the sensitivity of wave range with temperature in the Caspian Sea is more than that of the Oman Sea. This amount of range was seen at minimum and maximum temperatures of 9.74 and 24.30 degrees Celsius for the Caspian Sea, respectively 34 and 45.2 meters, and for the Oman Sea at temperatures of 22 and 32.2 degrees Celsius equal to 19.57 and 22 meters. The penetration depth of radar waves in the Caspian Sea can be three times higher than in the Oman Sea due to its low salinity. Since the range decreases with the increase in salinity, therefore, taking into account the salinity of the effluent of desalination facilities in the range of 74.8psu, the range of waves with a frequency of 100Hz has decreased sharply from 19.7m to 4m, which can be the cause of its tracking in the sea.